COVID-19 airborne transmission: a new frontier of infection - Banerjee, Indrajit; Robinson, Jared (Nepal Journal of Epidemiology, 2021)
COVID-19 has spread around the globe and infections are still rising despite the development of vaccinations and protocols. Various mutations of the SARS-CoV-2 virus have arisen with a greater rate of transmission and increased virulence. New found research has proven that the new strains of the virus are more virulent and use airborne aerosolized transmission to enable long range spread of the virus. By virtue of the fact that the virus spreads through such means, increases the risk of transmission and contamination highly as the virus can be transmitted via long range and through common ventilation and duct systems. In light of this it is now pertinent for legislation to support the use of personal protection equipment to safeguard the health of the public.